2003
DOI: 10.1017/s0003598x00092346
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the past: recent applications of multispectral imaging technology to deciphering manuscripts

Abstract: Multi-spectral imaging (MSI), which was developed to explore the surface of the earth and other planets from space, has been adapted to read and record faded or burnt manuscripts. The authors show how MSI achieved new readings from carbonised and damaged fragments of papyrus scrolls from Herculaneum, Petra and the Judean Desert. The method has potential for investigating the degraded ornamental surfaces of other artefacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 6 publications
(2 reference statements)
1
29
0
Order By: Relevance
“…In particular, the use of binocular microscopes, and digital photography, employing 'multispectral' filters that isolate a narrow portion of the near-infrared spectrum, have both improved the readability of these texts considerably 14,15 . Unfortunately, these techniques are not applicable to texts that remain rolled-up due to the superposition of papyrus layers and the weak penetration of most types of radiation exploited by multispectral techniques.…”
mentioning
confidence: 99%
“…In particular, the use of binocular microscopes, and digital photography, employing 'multispectral' filters that isolate a narrow portion of the near-infrared spectrum, have both improved the readability of these texts considerably 14,15 . Unfortunately, these techniques are not applicable to texts that remain rolled-up due to the superposition of papyrus layers and the weak penetration of most types of radiation exploited by multispectral techniques.…”
mentioning
confidence: 99%
“…The writing on the tablets is primarily preserved in the ink. The written material has been studied in depth using multispectral imaging (Booras and Seely, 1999;Chabries et al, 2003;Falcone et al, 2007). Our test with Polynomial Texture Mapping demonstrated that the differing surface textures of the wooden tablets and the ink lead to varying distribution of light by incident angle.…”
Section: Herculaneum Tablets and Wall Paintingmentioning
confidence: 94%
“…Almost all attempts resulted in failure and apparently very large numbers of the scrolls were lost. However exciting new imaging techniques have now made it possible to elucidate the text on similar scrolls (Baumann et al 2008;Chabries et al 2003).…”
Section: Writing Conservation 325mentioning
confidence: 99%